PENGEMBANGAN MEDIA PEMBELAJARAN ONLINE BERBASIS WEBSITE PADA MATERI LISTRIK DINAMIS - Irawan, Bambang; Maria, Haratua Tiur; Mursyid, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to develop learning media using website, and determinate the feasibility of learning media in the form website. This research is an R & D research that adopts the development of Borg &Gall that has been modified by Sugiono. Subjects in this research are students class IX SMPN 2 Pontianak. The type of data generated is qualitative data which is analyzed by guidance criteria of rating category to determine product quality using Likert scale. The results of this research are; 1) Produce website as a learning media; the product quality that has been developed is